2008
DOI: 10.1063/1.2939570
|View full text |Cite
|
Sign up to set email alerts
|

Rotational and vibrational state distributions of NaH in the reactions of Na(4S2,3D2,and6S2) with H2: Insertion versus harpoon-type mechanisms

Abstract: By using a pump-probe technique, the nascent rotational and vibrational state distributions of NaH are obtained in the Na(4 (2)S,3 (2)D, and 6 (2)S) plus H(2) reactions. The rotational distributions for the Na(4 (2)S,3 (2)D) reactions yield a bimodal feature with a major component peaking at J=20-22, similar to that obtained previously in the 4 (2)P reaction, whereas the Na(6 (2)S) reaction gives rise to a distinct distribution with a much lower rotational temperature. The vibrational populations (v=0-4) for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The reactions of excited-state alkali atoms with hydrogen molecule have received much attention because of their unique advantages for studying non-adiabatic processes in reaction dynamics. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] As the most intriguing characteristic, the alkali-hydrogen reactions are highly endoergic in their ground state. The energy to initiate the reaction is easily achieved via electronic excitation of the alkali atom, therefore the transitions of electronic states necessarily occur when the reaction proceeds from the excited entrance valley to the ground exit valley.…”
Section: Introductionmentioning
confidence: 99%
“…The reactions of excited-state alkali atoms with hydrogen molecule have received much attention because of their unique advantages for studying non-adiabatic processes in reaction dynamics. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] As the most intriguing characteristic, the alkali-hydrogen reactions are highly endoergic in their ground state. The energy to initiate the reaction is easily achieved via electronic excitation of the alkali atom, therefore the transitions of electronic states necessarily occur when the reaction proceeds from the excited entrance valley to the ground exit valley.…”
Section: Introductionmentioning
confidence: 99%
“…The NaH 2 presents a simple prototype of such collision systems, and numerous experimental results 1522 about the collisions between excited sodium atom and hydrogen molecule are available. Botschwina et al .…”
Section: Introductionmentioning
confidence: 99%
“…This experiment showed the formation of NaH via the Na(3p) + H 2 reaction follows a two-step mechanism, which is opposite to the direct reaction of Na(4p) + H 2. In 2008, Chang and co-workers 22 studied the rotational and vibrational state distributions of NaH in the reactions of high exited states Na(4 2 S, 3 2 D and 6 2 S) with H 2 by using the pump-probe technique. The authors concluded that the Na(6 2 S) reaction has a dramatically reduced ionization energy, and the corresponding reaction pathway maybe prefer a harpoon model via a near collinear configuration.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9], Rb (Refs. [19][20][21][22] and Li (Refs. 12-18) via a collinear approach geometry.…”
Section: Introductionmentioning
confidence: 99%